Screenshot: Lebih dari Sekedar Gambar, Bukti yang Berbicara - Aprilia Silvi Suciana; Yunan Prasetyo Kurniawan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Electronic money laundering has become a critical issue as a form of cybercrime. Advances in technology demonstrate that digital forensic applications, particularly those utilizing smartphones, can be employed to uncover digital traces of money laundering transactions. This study aims to analyze the relevance of existing legal frameworks, the effectiveness of smartphone forensic techniques, and the challenges faced in their implementation in Indonesia. Based on a review of the literature and regulatory analysis, it was found that legal frameworks such as UU No. 8 of 2010 on the Prevention and Eradication of Money Laundering (TPPU) and UU No. 19 of 2016 on Information and Electronic Transactions (ITE) provide an adequate legal foundation. However, gaps in implementation, such as limited human and technological resources, remain significant obstacles. Forensic techniques, including metadata analysis and device extraction, have shown great potential in identifying the flow of illicit funds. Nonetheless, their application is hindered by data confidentiality and the lack of uniform technical standards. Given the increasing complexity of digital crimes, an integrated approach is required, combining regulatory strengthening with technological capacity building, to enhance the effectiveness of smartphone forensics in addressing electronic money laundering.